Hepatoprotector in cases of dengue hemorrhagic fever as a prevention of hepatic damage: a case report - Emilia Gan; Yenry Sumarlim; Desantika Wuryana; M. Hari Pristantiningtyas; Herya Putra Dharma; Muhammad Muchlis; Jainuri Erik Pratama; Adji Prayitno Setiadi; Marisca Evalina Gondokesumo (Jurnal Teknologi Laboratorium)
Dengue Hemorrhagic Fever (DHF) is classified as an arbovirus disease which is a public health problem in the world. The causative agent of DHF is the dengue virus, namely the RNA virus of the genus Flavivirus and the family Flaviviridae. Hepatic impairment is often observed in DHF cases with asymptomatic or asymptomatic elevations in serum transaminases up to severe manifestations in the form of acute liver failure. It was reported that DHF patients had mild hepatic impairment with clinical manifestations of mild hepatomegaly, hypoalbumin, normal SGOT/SGPT values, and clinical conditions of nausea – vomiting. To prevent worsening liver damage, combination therapy with Ursodeoxycholic Acid (UDCA) and curcumin was given as a hepatoprotector. The use of curcumin can reduce serum levels of transaminase, Malondialdehyde (MDA) or markers of oxidative stress and increase hepatic glutathione concentrations which work in free radical detoxication, while the role of UDCA is as a hepatoprotector by reducing the level of oxidative stress in liver cells.